Assessment Of Environmentally Friendly Building Criteria By Using Sample Fuzzy Additive Weighting (Fsaw) Method To Support Energy-Saving Movement(Study: Office Building Pringsewu District) - Danang Kusnadi; Pamuji Setiawan; Ida Ayu Putu Anggie Sinthiya (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The recent energy crisis forces everyone to have a conscious awareness of energy. Energy-saving activities can be done in various ways such as turning off unused lights, turn on television as necessary and many more activities undertaken one of them is building a building that has an environmentally friendly concept. The purpose of knowing the rating / certification as a benchmark has been how far the level of application of green building criteria office buildings in Pringsewu District. The research used qualitative and quantitative descriptive method and by using Fuzzy Sample Additive Weighting Analysis (FSAE). The result of research shows that so far the application of environmentally friendly building in Pringsewu District Office Building has not been done completely, based on 27 items of environmental friendly building assessment criteria, there are only few categories that can be fulfilled either in the concept of building and the concept of the manager or the occupant of building. Keywords : Environmentally Friendly Building, and FSAW.